2017
DOI: 10.1108/sgpe-d-17-00014
|View full text |Cite
|
Sign up to set email alerts
|

“Me-search”

Abstract: Purpose -The purpose of this paper is to discuss the experiences with me-search among scholars in the field of education, defined as the conduct of research about one's own identity or in one's own setting.Design/methodology/approach -Centered around the tensions inherent in the training received around objectivity and subjectivity, these individuals discuss how they came to conduct me-search and the challenges inherent in it, with a particular focus on the teaching and advising of students conducting this kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…According to Ragins (2008), the decision to disclose stigmatized identities depends on many factors, including centrality to one's identity. Sometimes referred to as "mesearch" (Gardner et al, 2017) or "self-relevant research" (Devendorf, 2020), academics, especially social scientists, tend to research topics they have a personal stake in or experience with (Ross et al, 2020). On several occasions, I found that concealment prevented me from fully engaging with my research colleagues and participants.…”
Section: Disclosing As a Researchermentioning
confidence: 99%
“…According to Ragins (2008), the decision to disclose stigmatized identities depends on many factors, including centrality to one's identity. Sometimes referred to as "mesearch" (Gardner et al, 2017) or "self-relevant research" (Devendorf, 2020), academics, especially social scientists, tend to research topics they have a personal stake in or experience with (Ross et al, 2020). On several occasions, I found that concealment prevented me from fully engaging with my research colleagues and participants.…”
Section: Disclosing As a Researchermentioning
confidence: 99%
“…Doctoral students' challenge is more than just telling their story, however. They need to begin to write their own story, putting the "me" in the "me-search" of constructing their scholarly identity in their context (Gardner et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Those who hold multiple minoritized identities describe the ways others respond to their embodiment and performance, compounding the marginality they experience with intense self-consciousness (Eguchi & Spieldenner, 2015). While navigating hostile academic environments, many racially minoritized faculty with other multiple minoritized identities also experience their teaching, scholarship, and service to be valued less than their white colleagues, and often seen as not rigorous or objective (Gardner et al, 2017). Racially minoritized LGBTQ+ faculty, for example, struggle to navigate structural racism, queerphobia, and sexism in institutions of higher education which is a larger reflection of US society (Stewart, 2014).…”
Section: Experiences Of Racially Minoritized and Lgbtq+ Facultymentioning
confidence: 99%